Dinamika Konflik Agraria di Wilayah Pesisir : Studi Kasus Akuisisi Lahan oleh Universitas Pertahanan di Pantai Atapupu Desa Jenilu Kabupaten Belu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Agrarian conflict is a common issue in development processes, particularly when changes in land ownership or control involve various interests. This study aims to analyze the dynamics of agrarian conflict in the coastal area of ​​Atapupu Beach, Jenilu Village, Kakuluk Mesak District, Belu Regency, triggered by the land acquisition process by the Defense University (UNHAN). The study used a qualitative approach with a case study method to understand the social conditions developing in the community. Data were obtained through in-depth interviews, field observations, and documentation. The results indicate that the conflict arose due to changes in community access to coastal areas previously used for economic activity. The presence of UNHAN has restricted community activities in the Fish Auction Place (TPI) area, previously a center for fishing activities. This situation has given rise to social tensions between the community and the area management. This study emphasizes that coastal area management needs to consider local community interests through a dialogical and participatory approach to minimize agrarian conflict.